(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Writing an autobiography is an exercise in knowing the self. As women in the phallocentric discourse have always been written about, a woman’s autobiography assumes special significance. The paper seeks to engage with Amrita Pritam’s autobiography challenges the stereotypes created by the androcentric discourse about the creativity of women as patriarchy belittles the importance of women’s achievements. Her autobiography marks a refusal to be described and portrayed by hegemonic male narratives as she explores her personal and literary journey through her own agency.